Strategic approach to developing a self-microemulsifying drug delivery system to enhance antiplatelet activity and bioavailability of ticagrelor - Na YG (Dove Medical Press, 2019)
Young-Guk Na,1 Jin-Ju Byeon,1 Miao Wang,1 Hyun Wook Huh,1 Gi-Ho Son,1,2 Sung-Hoon Jeon,1,3 Ki-Hyun Bang,1,2 Sung-Jin Kim,1 Hye-Jin Lee,1 Hong-Ki Lee,1 Cheong-Weon Cho1 1College of Pharmacy, Chungnam National University, Daejeon, Republic of Korea; 2Korea United Pharmaceutical Co. Ltd., Sejong, Republic of Korea; 3SamA Pharmaceutical Co. Ltd., Suwon, Republic of Korea Background: Ticagrelor (TCG) is used to inhibit platelet aggregation in patients with acute coronary syndrome, but its poor solubility and low bioavailability limit its in vivo efficacy. The purpose of this study was to manufacture an optimized TCG-loaded self-microemulsifying drug delivery system (SMEDDS) to enhance the oral bioavailability and antiplatelet activity of TCG. Materials and methods: Solubility and emulsification tests were conducted to determine the most suitable oils, surfactants, and cosurfactants. Scheffé’s mixture design was applied to optimize the percentage of each component applied in the SMEDDS formulation to achieve optimal physical characteristics, ie, high solubility of TCG in SMEDDS, small droplet size, low precipitation, and high transmittance. Results: The optimized TCG-loaded SMEDDS (TCG-SM) formulation composed of 10.0% Capmul MCM (oil), 53.8% Cremophor EL (surfactant), and 36.2% Transcutol P (cosurfactant) significantly improving the dissolution of TCG in various media compared with TCG in Brilinta® (commercial product). TCG-SM exhibited higher cellular uptake and permeability in Caco-2 cells than raw TCG suspension. In pharmacokinetic studies in rats, TCG-SM exhibited higher oral bioavailability with 5.7 and 6.4 times higher area under the concentration–time curve and maximum plasma concentration, respectively, than a raw TCG suspension. Antiplatelet activity studies exhibited that the TCG-SM formulation showed significantly improved inhibition of platelet aggregation compared with raw TCG at the same dose of TCG. And, a 10 mg/kg dose of raw TCG suspension and a 5 mg/kg dose of TCG-SM had a similar area under the inhibitory curve (907.0%±408.8% and 907.8%±200.5%·hours, respectively) for antiplatelet activity. Conclusion: These results suggest that the developed TCG-SM could be successfully used as an efficient method to achieve the enhanced antiplatelet activity and bioavailability of TCG. Keywords: ticagrelor, SMEDDS, optimization, bioavailability, platelet aggregation, antiplatelet activity